2018
DOI: 10.4103/jehp.jehp_177_17
|View full text |Cite
|
Sign up to set email alerts
|

Development an Electronic Oral Health Record application for educational dental setting

Abstract: AIM:Worldwide, the adoption of electronic patient recording system is increasing among many parts of the health sectors. Although paper-based recording of patients’ information was a routine in many departments of dental schools, easy destruction of collected information and the costs of its conversion to electronic data, limited the availability of updated data at the department of dental public health. This paper aimed to explain the project of designing a system for Electronic Oral Health Recording (EOHR) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 9 publications
(7 reference statements)
0
6
0
Order By: Relevance
“…The questionnaire was adopted from previously conducted similar studies and modified to fit with the current set-up. 16,20 The data were collected by two data collectors who were well briefed about the data collection procedure and the purpose of the study. The questionnaire composed of four parts: socio-demographic characteristics (9 questions), knowledge-related questions (10 questions), attitude-related questions (8 questions), and practice-related questions (13 questions) respectively.…”
Section: Data Collection Tool and Techniquementioning
confidence: 99%
“…The questionnaire was adopted from previously conducted similar studies and modified to fit with the current set-up. 16,20 The data were collected by two data collectors who were well briefed about the data collection procedure and the purpose of the study. The questionnaire composed of four parts: socio-demographic characteristics (9 questions), knowledge-related questions (10 questions), attitude-related questions (8 questions), and practice-related questions (13 questions) respectively.…”
Section: Data Collection Tool and Techniquementioning
confidence: 99%
“…It was seen through our overview that lone 11% professionals of Lahore recorded case history digitally. The attention to keeping up record digitally should be expanded as it is the most effortless route as to support for a more drawn out timeframe and requires less space too 29 .…”
Section: Discussionmentioning
confidence: 99%
“…The relatively low cost, its portable nature and the ease of access to wireless networks where there is network range make these implements very attractive to users. 14 The results of Asgari's 15 research in Iran showed that electronic dental health records could provide benefits with regards to storage, processing and data utilisation, which were all major components in delivering effective and efficient service based on the available evidence. Digital versions of these records are more effective and efficient because they reduce paperwork, lead to the fast processing of data, facilitate ease of analysis and increase the accuracy, precision and quality of data.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, dental and oral health data records can be used in conjunction with programme planning and intervention. 15 In relation to this, Petersen et al 16 found in their research that in constructive health-related decision-making and planning, the information system must cover aspects of risk factors associated with oral health and the quality of information related to it, services and interventions, administrative processes and the quality of clinical care outcomes as well as epidemiological details.…”
Section: Discussionmentioning
confidence: 99%